Community Socialization and Training for Waste Management and Productive Household Composting - Rezki Aguswidya Utami; Setyo Kuncoro; Agus Priyanto; Adisthy Shabrina Nurqamarani; Abdurrahman Rahim Thaha; Arie Aryanto (Jurnal Abdimas Mahakam, 2025)
Waste management is one approach to achieving a greener future. It is also related to SDGs 11 and 12 regarding sustainable cities and communities, as well as responsible consumption and production. Tonjong village is one of the villages in Tajur Halang District, Bogor, which faces significant challenges in managing the large volume of household waste, much of which remains unprocessed. To address this issue, the Business Administration Program, Faculty of Law, Social and Political Sciences (FHISIP), Universitas Terbuka, launched a community service program aimed at improving household waste management through socialization of waste management and composting training in Tonjong village. There are fifteen participants in the community service, including residents of Tonjong village, four neighborhood units, one representative from the neighborhood association, farmers' members, and administrators from Bank Sampah. The outcome of this program is increased ecological literacy and increased awareness among participants in managing waste and processing organic waste into compost. This initiative not only supports better environmental practices but also creates opportunities for the community to generate income by selling compost, with proceeds used to fund future community activities.